Reading medieval European women writers strong literary witnesses from the past - Classen, Albrecht 1956- (Peter Lang Edition, 2016)
"Despite a modern tendency to describe medieval women as suppressed and marginalized, a critical reading of relevant texts by female poets/writers demonstrates that women all over Europe in the premodern era enjoyed considerable freedom to express themselves and to contribute to the literary discourse of their time. This book brings together representative poets from Germany, England, France, Spain, Hungary, and Austria and thus develops an innovative pan-European perspective spanning from the tenth to the sixteenth century. Well-known writers are as much included as some rather little studied individuals, who all form part of a strong choir of female voices."...
Includes bibliographical references
Keywords: Geschichte 950-1500; Literature, Medieval -- Women authors -- History and criticism; Women in literature; Frauenliteratur; Europa